PENGARUH KARAKTERISTIK KEWIRAUSAHAAN TERHADAP KINERJA USAHA MIKRO DAN KECIL MELALUI PENERAPAN MANAJEMEN USAHA DI KOTA JAMBI - Agus Syarif; Istiqomah Malinda SB; Maulidia Imastary Tan; Agesha Marsyaf (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
This study aims to analyze the effect of entrepreneurial characteristics on the performance of Micro and Small Enterprises through the application of business management in Jambi City. The approach used is descriptive quantitative. Samples were taken as many as 99 micro and small business actors. The data used in this study are primary and secondary data. The findings from the research show that there is a significant effect of entrepreneurial characteristics on performance on the implementation of micro and small business management in Jambi City. Entrepreneurial characteristics also affect the performance of micro and small businesses through the application of business management, both in the management and management functions. Keywords: Entrepreneurial characteristics, Management, Performance and Micro Small Enterprises.